2011
DOI: 10.1097/qad.0b013e328341afa8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of protective antibody response by MF59-adjuvanted 2009 pandemic A/H1N1v influenza vaccine in HIV-1-infected individuals

Abstract: a single dose of MF59-adjuvanted 2009 influenza H1N1 vaccine induced an immune response against pandemic H1N1 virus in HIV-1-positive individuals reaching titers similar to those of HIV-1-negative individuals. The seroconversion rate was negatively associated with HIV infection and increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 24 publications
3
17
1
Order By: Relevance
“…22,23 In contrast, other work has suggested a lower response in HIV-infected individuals, even in successfully treated patients. [18][19][20] It may be speculated that the apparent discrepancy is mainly attributable to the baseline level of reactivity to influenza virus antigen that is clearly higher in the HIV group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 In contrast, other work has suggested a lower response in HIV-infected individuals, even in successfully treated patients. [18][19][20] It may be speculated that the apparent discrepancy is mainly attributable to the baseline level of reactivity to influenza virus antigen that is clearly higher in the HIV group.…”
Section: Discussionmentioning
confidence: 99%
“…17 In pandemic A/H1N1 influenza vaccine studies, the data are contrasting. In fact, several studies on the efficacy of MF59-adjuvanted 2009 pandemic A/H1N1 influenza vaccine (A/H1N1/Cal/09) suggested a lower rate of influenza seroconversion in HIV-infected individuals (36.4-69%) as compared with healthy donors ( > 79%), [18][19][20] even in patients with high CD4 T cell counts. 21 In contrast, other studies reported a good antibody response in successfully HAART-treated HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…[267,268] These findings of reduced immunogenicity extend to adjuvanted vaccines (AS03 and MF-59) among HIV-positive compared to HIV-negative individuals. [269][270][271] Two systematic reviews conducted on the effectiveness of influenza vaccines among HIV-positive populations showed limited evidence of VE in this population and called for more data from RCT settings. [12,13] However, a recent RCT of TIV among HIV-infected adults in South Africa showed a vaccine efficacy of 76% and high levels of serological conversion.…”
Section: Disease Burdenmentioning
confidence: 99%
“…Several clinical trials of A/H5N1 vaccines containing A/Vietnam/1194/2004 strain antigen have shown that, as well as decreasing the amount of antigenic material required per dose (7), the oil-in-water adjuvant MF59 (Novartis Vaccines and Diagnostics) increases the production of cross-reactive, neutralizing antibodies (13, 14, 18-20, 24, 28). The ability of MF59 to enhance antigenspecific and cross-reactive antibody responses has been demonstrated in vaccinees of all ages, including the elderly (2,12,33,34) and other high-risk populations (1,8,9,17,22,30,39).…”
mentioning
confidence: 99%